Carbohydrate Level and Growth of Tomato Plants: II. The Effect of Irradiance and Temperature - Gent, Martin P. N. (1986)
The growth response of tomato (Lycopersicon esculentum L.) to temperature and irradiance may be related to carbohydrate concentration. Plants in the exponential phase of vegetative growth were grown under temperatures ranging from 9 to 36°C and under low or high irradiances of approximately 110 or 370 microeinsteins per square meter per second photosynthetically active radiation for a 12 hour photoperiod. The relative growth rate, leaf area ratio, net assimilation rate and whole plant carbohydrate levels were measured. At high irradiance, relative growth rate was 43% faster and total nonstructural carbohydrate concentration was 41% greater than at low irradiance. The change in carbohydrate with irradiance could explain the growth response. Plant growth was fastest at 25°C and decreased parabolically at lower and higher temperatures with a half-maximal rate at 13 and 36°C. Total nonstructural carbohydrate decreased between 13 and 23°C and remained constant at higher temperatures. Soluble sugar concentrations varied little with temperature above 13°C except for sucrose, whose level rose above 30°C. The change in carbohydrate with temperature could not explain the growth response. Above 23°C tomato plants appeared to regulate growth rate to maintain a relatively constant nonstructural carbohydrate concentration.